The Longitudinal Impact of an Internet Safety Decision Aid for Abused Women - Glass, Nancy E.; Perrin, Nancy A.; Hanson, Ginger C.; Bloom, Tina L.; Messing, Jill T.; Clough, Amber S.; Campbell, Jacquelyn C.; Gielen, Andrea C.; Case, James; Eden, Karen B. (American journal of preventive medicine, 2017)
Women experiencing intimate partner violence (IPV) navigate complex, dangerous decisions. Tailored safety information and safety planning, typically provided by domestic violence service providers, can prevent repeat IPV exposure and associated adverse health outcomes; however, few abused women access these services. The Internet represents a potentially innovative way to connect abused women with tailored safety planning resources and information. The purpose of this study was to compare safety and mental health outcomes at baseline, 6 months, and 12 months among abused women randomized to: (1) a tailored, Internet-based safety decision aid; or (2) control website (typical safety information available online). Multistate, community-based longitudinal RCT with one-to-one allocation ratio and blocked randomization. Data were collected March 2011–May 2013 and analyzed June–July 2015. Currently abused Spanish- or English-speaking women (N=720). A tailored Internet-based safety decision aid included priority-setting activities, risk assessment, and tailored feedback and safety plans. A control website offered typical safety information available online. Primary outcomes were decisional conflict, safety behaviors, and repeat IPV; secondary outcomes included depression and post-traumatic stress disorder. At 12 months, there were no significant group differences in IPV, depression, or post-traumatic stress disorder. Intervention women experienced significantly less decisional conflict after one use (β= –2.68, p=0.042) and greater increase in safety behaviors they rated as helpful from baseline to 12 months (12% vs 9%, p=0.033) and were more likely to have left the abuser (63% vs 53%, p=0.008). Women who left had higher baseline risk (14.9 vs 13.1, p=0.003) found more of the safety behaviors they tried helpful (61.1% vs 47.5%, p<0.001), and had greater reductions in psychological IPV ((11.69 vs 7.5, p=0.001) and sexual IPV (2.41 vs 1.25, p=0.001) than women who stayed. Internet-based safety planning represents a promising tool to reduce the public health impact of IPV.